2022
DOI: 10.3390/diseases10020034
|View full text |Cite
|
Sign up to set email alerts
|

Metals and Metallothionein Expression in Relation to Progression of Chronic Kidney Disease of Unknown Etiology (CKDu) in Sri Lanka

Abstract: Chronic kidney disease of unknown etiology was investigated for metal relations in an endemic area by a cross-sectional study with CKD stages G1, G2, G3a, G3b, G4, G5 (ESRD), and endemic and nonendemic controls (EC and NEC) as groups. Subjects with the medical diagnosis were classified into groups by eGFR (SCr, CKD-EPI) and UACR of the study. It determined 24 metals/metalloids in plasma (ICPMS) and metallothionein (MT) mRNA in blood (RT-PCR). MT1A at G3b and MT2A throughout G2–G5 showed increased transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Males dominate over females by 1.2 to more than 3 : 1; rarely female individuals slightly predominate in select geographic regions [4,13]. The age at initial diagnosis is 20–60 years, with Asian patients trending older than those in Central America [3 ▪▪ ,8,13,14]. Sugarcane farming confers increased risk for CKDu in Central America while in Asia, it is rice paddy work [15].…”
Section: Demographics and Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Males dominate over females by 1.2 to more than 3 : 1; rarely female individuals slightly predominate in select geographic regions [4,13]. The age at initial diagnosis is 20–60 years, with Asian patients trending older than those in Central America [3 ▪▪ ,8,13,14]. Sugarcane farming confers increased risk for CKDu in Central America while in Asia, it is rice paddy work [15].…”
Section: Demographics and Clinical Featuresmentioning
confidence: 99%
“…However, other studies have shown rice with acceptable levels of lead, cadmium, and arsenic consumed by CKDu patients, suggesting this is not a primary disease mechanism [33]. Heavy metals and/or trace elements can contaminate agrochemicals resulting in simultaneous nephrotoxin exposures [14]. High fluoride levels have been found in black tea and groundwater in CKDu hot spots [6,7 & ].…”
Section: Wwwco-nephrolhypertenscommentioning
confidence: 99%